Imagery Training Method and Hand-Eye Coordination on The Exercise of Ball Batting Practice of Softball-Baseball of UNNES (Journal of Physical Education and Sports, 2019)
The purpose of this study was to determine the effect of Imagery training methods and hand-eye coordination on the exercise of ball batting practice of softball on the softball-baseball student's activity unit athletes of UNNES. The research method was using an experiment with a 2x2 factorial design. The sample was 22 athletes were taken by using purposive sampling technique. The instrument for a test of hitting the ball is Elrod softball batting tests of Johnson BL and Nelson JK, eye-hand coordination by catching-throwing tennis balls at a wall that had been given a target by Ismaryati in Tatag Efendi. Data analysis technique was using ANOVA with two lanes. The results showed that Imagery training methods (exercises internal and external imagery) effected on the result of batting practice balls softball-baseball students activity unit athletes of UNNES there were differences of influence between the level of hand-eye coordination high and low on the results of batting practice balls softball on the softball-baseball students activity unit athletes of UNNES and there were interactions between imagery training method (exercise internal imagery and external imagery) and hand-eye coordination (high and low) on the results of ball batting practice of softball on the softball-baseball students activity unit athletes of UNNES. The conclusion the imagery internal exercise had better influences on the results of a softball batting practice.